Efektivitas Strategi Pemasaran Bank Syariah dalam Menarik Nasabah (Studi Kasus di Bank Syariah Indonesia KC Pekanbaru Harapan Raya) - Yetti, Febri Delmi (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to analyze the effectiveness of relationship-based, education, and digital marketing strategies implemented by BSI KC Pekanbaru Harapan Raya, identify supporting and inhibiting factors, evaluate their impact on trust, loyalty, and increasing the number of customers, and provide strategic recommendations to optimize marketing and improve bank competitiveness. A qualitative approach with a phenomenological method with secondary data includes bank documents and related literature. Data analysis was carried out with steps of reduction, theme grouping, and interpretation to understand the meaning of respondents' experiences and relate the findings to sharia marketing theory. This study shows that BSI KC Pekanbaru Harapan Raya's marketing strategy is effective in attracting customers with a personal approach, sharia financial education, digital media, and local community partnerships. The main supporting factors include increasing public awareness of sharia finance, government regulations, and digital innovation. However, challenges such as lack of public understanding, limited service networks, and competition with conventional banks remain, although relationship marketing plays an important role in building customer trust and loyalty.